2009
DOI: 10.1016/j.devcel.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The FERM-Domain Protein Expanded Regulates Hippo Pathway Activity via Direct Interactions with the Transcriptional Activator Yorkie

Abstract: The Hippo kinase pathway plays a central role in growth regulation and tumor suppression from flies to man. The Hippo/Mst kinase phosphorylates and activates the NDR family kinase Warts/Lats, which phosphorylates and inhibits the transcriptional activator Yorkie/YAP. Current models place the FERM-domain protein Expanded upstream of Hippo kinase in growth control. To understand how Expanded regulates Hippo pathway activity, we used affinity chromatography and mass spectrometry to identify Expanded-binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
196
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(206 citation statements)
references
References 42 publications
8
196
2
Order By: Relevance
“…S2 A and C). Ex has been shown to inhibit Yki independent of Wts by sequestering it at the plasma membrane (82,83). However, we did not observe changes of Kib protein levels in ex e1 mutant clones in the brain (Fig.…”
Section: Significancementioning
confidence: 53%
“…S2 A and C). Ex has been shown to inhibit Yki independent of Wts by sequestering it at the plasma membrane (82,83). However, we did not observe changes of Kib protein levels in ex e1 mutant clones in the brain (Fig.…”
Section: Significancementioning
confidence: 53%
“…In overexpression studies in cultured cells, Wts, Ex and Hpo can interact with Yki and repress its activity in a phosphorylation-independent mechanism. 31,32 We found that Wbp2 depletion reduced overgrowth of tissues harbouring amorphic alleles of wts, showing that Wbp2 exerts an effect epistatically to Wts. Therefore, Wbp2 does not activate Yki by interfering with Wts-mediated Yki repression, whether it is dependent or independent of phosphorylation.…”
Section: Discussionmentioning
confidence: 89%
“…The nuclear accumulation of Yorkie is consistent with a loss of function in these experiments. Yorkie is the substrate of the Hippo signaling pathway regulated by Merlin and Expanded (12,(21)(22)(23). Therefore, restriction of motor-driven transport of an otherwise normal WT Merlin protein by an NF2 mutant protein results in the loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, mutation of a single threonine residue (T616) changes its distribution and association with various ligands, such as Moesin, another member of the ERM family (20). Both in vivo and in cultured cells, Merlin together with Expanded, have been shown to regulate cell growth and differentiation by promoting phosphorylation and cytoplasmic retention of the transcriptional coactivator Yorkie/YAP1 (12,(21)(22)(23). Moreover, recent studies suggest that through localization at the cortical actin network, Merlin controls the internalization and signaling of certain membrane receptors, including the epidermal growth factor (6, 9, 24-27).…”
mentioning
confidence: 99%